Capital in Disequilibrium : the Role of Capital in a Changing World. - Lewin, Peter (Routledge foundations of the market economy., 1998)
Drawing on the work of the Austrian School and its heirs, Capital in Disequilibrium develops a modern, systematic version of capital theory in order to suggest a new approach to the subject of economics.